O uso de documentos eletrônicos na contabilidade - Pasa, Eduardo Cesar (Revista Contabilidade & Finanças, 2001)
The main objective of this article is to elaborate some thoughts on electronic documents used in corporate accounting. This article is a quick summary of how electronic documents have been treated by corporate regulatory agencies in the USA.The article also intends to create concepts and verify the foundations of the documents, that is, electronic documents and accounting documents. Therefore, rules and laws were verified, as well as Law Projects related to the issue. The results show a transition period in accordance with paradigm changes, which are a result of the new economy. Additionally, it reveals some problems such as a lack of specific legislation in the use of electronic documents in accounting.